Estimating Endocranial Volume in the Domestic Cat (Felis catus) Using Computed Tomography - Ebru Eravci Yalin; Sedat Aydoğdu; Ozan Gündemir; Mehmet Saadeddin Öztürk; Margot Michaud (Iranian Journal of Veterinary Surgery)
Changes in brain and endocranial volume size are observed in most mammals during domestication. However, while much attention has been paid to comparing domesticated species with their wild relatives, few studies have focused on the differences between domesticated breeds, especially in cats. In this study, we estimated the endocranial volume of two different domestic cat breeds (Felis catus) using virtual endocasts obtained from computed tomography (CT) images. Our analysis did not reveal any significant differences between the British Shorthair and the Scottish Fold domestic breeds in terms of endocranial volume. In addition, we found similar results with volumes previously obtained from domestic cats using bead methods. Although these results represent only a limited sample of the entire cat breed diversity, we hope they will contribute to our understanding of the macroevolutionary changes in brain volume during domestication.